2017
DOI: 10.18203/issn.2454-2156.intjscirep20173092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and intervention of students’ laboratory performance in chemistry graduating classes; Wachemo University, Ethiopia

Abstract: <p class="abstract"><strong>Background:</strong> The laboratory courses offer students the opportunity to gain manipulative skills, observational skills, and the ability to plan experiments and to interpret experimental data. The laboratory can be an excellent environment for active learning. It has long been considered useful to develop conceptual understanding, but some recent courses have been developed that rely heavily on laboratory experience, in contrast to conventional teaching method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Students taught this way tended to just follow instructions without much thought (White, 1990). In addition, studies have found that students experienced low motivation in the qualitative analysis classrooms because of the demanding nature of the qualitative analysis lessons, whereby students said that they felt 'irritated' with the demanding memory work (Tan, 2005;Tan et al, 2001) and the presence of too much 'noise' (due to the demand of handling many things at once) during the practical session in the laboratory (Gebrehiwot, 2017). Such simultaneous cognitive demands resulted in a loss of interest in the practical task of learning about how to carry out a qualitative analysis.…”
Section: Causes Of Difficulties In Learning and Understanding Qualitative Analysis In Chemistrymentioning
confidence: 99%
“…Students taught this way tended to just follow instructions without much thought (White, 1990). In addition, studies have found that students experienced low motivation in the qualitative analysis classrooms because of the demanding nature of the qualitative analysis lessons, whereby students said that they felt 'irritated' with the demanding memory work (Tan, 2005;Tan et al, 2001) and the presence of too much 'noise' (due to the demand of handling many things at once) during the practical session in the laboratory (Gebrehiwot, 2017). Such simultaneous cognitive demands resulted in a loss of interest in the practical task of learning about how to carry out a qualitative analysis.…”
Section: Causes Of Difficulties In Learning and Understanding Qualitative Analysis In Chemistrymentioning
confidence: 99%